Academic resilience in mathematics among junior high school students - Bela Negara, Adinda; Atmoko, Adi; Wahyuni, FItri (Psychology, Evaluation, and Technology in Educational Research, 2025)
Academic resilience is an important aspect of education. With academic resilience, students are better equipped to face obstacles, pressure, and challenges in mathematics learning. This study aims to provide an overview of students' academic resilience levels in mathematics at Junior High School 1 Plosokaten Kediri and serve as a reference for school counselors in developing guidance and counseling programs. Using a survey method and descriptive statistical analysis, the data is presented in percentage tables for each aspect of academic resilience. The results show that communication and collaboration scored 71.60% (moderate), self-efficacy 61.31% (low), empathy 68.31% (moderate), problem-solving 58.84% (low), self-awareness 62.96% (low), and aspirations and goals 72.01% (moderate). This condition implies the need for more varied and innovative guidance and counseling strategies, rather than relying solely on lectures and motivational approaches. Group guidance services using various techniques such as simulation games, role-playing, modeling, reframing, Problem-Based Learning, and the Solution-Focused Brief Counseling approach can serve as effective alternatives to enhance each aspect of academic resilience. The implementation of these strategies is expected to develop students’ communication skills, empathy, self-awareness, and strengthen self-efficacy, aspirations, and problem-solving abilities, enabling them to become more adaptive, confident, and resilient in facing the challenges of learning mathematics.